1988
DOI: 10.1128/jvi.62.8.2622-2628.1988
|View full text |Cite
|
Sign up to set email alerts
|

Purified envelope glycoproteins from human immunodeficiency virus type 1 variants induce individual, type-specific neutralizing antibodies

Abstract: Repeated immunizations of goats, horses, or chimpanzees with envelope glycoprotein gpl20 isolated from human immunodeficiency virus type 1 (HIV-1) resulted in type-specific neutralizing-antibody responses, which began to decay approximately 20 days following the administration of antigen. This was true repeatedly for serum samples from animals hyperimmunized with gpl20s from either the HTLV-IIIB (IIIB) or the envelope-divergent HTLV-IIIRF (RF) HIV-1 isolates. Animals previously immunized with the IIIB gpl20 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Initial immunization studies demonstrated that although high anti-Env titers are inducible, the neutralization phenotype of both sera and isolated mAbs is limited (Robey et al, 1986; Berman et al, 1988; Ho et al, 1988; Nara et al, 1988; Earl et al, 1989; Haigwood et al, 1990). Given the largely unsuccessful immunizations with monomeric gp120 (Berman et al, 1990; Wrin et al, 1995; Mascola et al, 1996; Barnett et al, 1997; Belshe et al, 1998; Connor et al, 1998), attempts have been made to present the immune system with a more accurate representation of the neutralizing epitopes displayed on functional HIV Env spike by using trimeric Env.…”
Section: Hiv Neutralizing Responses After Animal Immunization: Successes and Failuresmentioning
confidence: 99%
“…Initial immunization studies demonstrated that although high anti-Env titers are inducible, the neutralization phenotype of both sera and isolated mAbs is limited (Robey et al, 1986; Berman et al, 1988; Ho et al, 1988; Nara et al, 1988; Earl et al, 1989; Haigwood et al, 1990). Given the largely unsuccessful immunizations with monomeric gp120 (Berman et al, 1990; Wrin et al, 1995; Mascola et al, 1996; Barnett et al, 1997; Belshe et al, 1998; Connor et al, 1998), attempts have been made to present the immune system with a more accurate representation of the neutralizing epitopes displayed on functional HIV Env spike by using trimeric Env.…”
Section: Hiv Neutralizing Responses After Animal Immunization: Successes and Failuresmentioning
confidence: 99%
“…An effective vaccine based upon gp120 must be capable 881 of eliciting an immune response against a wide range ofHIV-1 envelope glycoproteins. Yet previous studies have shown that immunizations with envelope protein derived from a single isolate of HIV-1 generally did not induce a broadly crossreactive antibody response (18)(19)(20) . In the present work, a chamber ELISA was developed to investigate the crossreactivity of individual B cells activated in mice immunized with gp120s from different isolates of HIV Results indicate that 85-95% of the B cells activated after immunization with a single isolate of gp120 reacted only with that isolate.…”
mentioning
confidence: 92%
“…Neutralizing antibodies that arise early in infected humans and that are readily generated in animals by immunization with gp120 or gpl60 preparations are primarily directed against linear determinants in the V3 loop of the gp120 glycoprotein (35, 47, 48, 55, 64-66, 69, 71). These antibodies generally exhibit the ability to neutralize only a limited number of HIV-1 strains (23,48,57,61), although a subset of anti-V3 antibodies recognize less variable elements of the region and therefore exhibit broader neutralizing activity (1, 24a, 34, 42, 58). Envelope glycoprotein variation within the linear V3 epitope and outside of the epitope can allow escape of viruses from neutralization by these antibodies (50, 56).…”
mentioning
confidence: 99%